ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI KEUNGGULAN UNWAHAS TERHADAP MINAT MENJADI MAHASISWA PADA UNIVERSITAS WAHID HASYIM SEMARANG - . Wachjuni (Universitas Wahid Hasyim, 2010)
Changes that occured in the global business environment increase the competition among higher education institutions. Each of the institutions attempting to offer higher services performance and showing the benefits, the uniqueness, and the competence of the institutions in order to fullfil the need of the community. Highly competition among private college has a positive impact in improving their service and education quality, but in opposite have a negative impact in decreasing the number of students at many private universities, and increasing the bankruptcy risk of the college. In general, private college depends on their student fees. It needs a hard effort to get to maintain as well as get students. This study analyzes the iinterest of students in institution’s image and competitive advantages of Wahid Hasyim Semarang University. Research problems emerge from 2 (two) things: first, it comes from research gap from previously research literature, eg, referring to the limitations and research directions and inconsistence results of the previous findings such as the Thomas E. Decarlo.dkk; Jyh-Shen Chiou and Cornelia Droge (2006), Shue-Ching Hong, and YJ James Goo (2004), Yoo et al. (2000), Dodds et al. (1991), Radnor and Lovell (2003), Grewal, Monroe, and Krishan (1998). The second problem comes from the data found that provide overall excellence and interest of the Wahid Hasyim University students. This research was conducted to determine the factors that influence the institutions image and brand that will increase the Perceived Quality of Unwahas excellency. This research developed a theoretical model in proposing four hypotheses and examined using Structural Equation Model (SEM). The 150 respondents used in this study were taken from students at the University Wahid Hasyim. Keywords: corporate image, brand Perceived Quality, excellence Unwahas, student interest